2017
DOI: 10.1155/2017/6716053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Addition of Propolis Extract on Bioactive Compounds and Antioxidant Activity of Craft Beer

Abstract: Antioxidant-rich foods and beverages play an essential role in the prevention of diseases. This study assessed the influence of the addition of ethanolic extract of propolis (EEP) to beer at different concentrations (0.05, 0.15, and 0.25 g/L). Total phenolic content (TPC) and total flavonoid content (TFC) were determined. Antioxidant activity (AA) was evaluated by radical scavenging activity (DPPH and ABTS) and reducing power (FRAP). The addition of EEP in beer resulted in a linear increase in the TPC with val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
29
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 42 publications
9
29
2
4
Order By: Relevance
“…Our search of the PubMed and Scielo.org databases discovered no works that scientifically evaluated the potential of adding propolis to beer for preservation. Some researchers 28 have observed that the addition of ethanolic extract produced an increase in the antioxidant potential of beer, without altering the organoleptic characteristics of Golden Ale (high fermentation) type beer.…”
Section: Discussionmentioning
confidence: 99%
“…Our search of the PubMed and Scielo.org databases discovered no works that scientifically evaluated the potential of adding propolis to beer for preservation. Some researchers 28 have observed that the addition of ethanolic extract produced an increase in the antioxidant potential of beer, without altering the organoleptic characteristics of Golden Ale (high fermentation) type beer.…”
Section: Discussionmentioning
confidence: 99%
“…Propolis is a natural product that has many functional properties such as antioxidant, antibacterial, anticancer, antifungal, anti-inflammatory and antiviral activities. The incorporation of propolis extract in beer reduces oxidation and fortifies the phenolic content that is typically reduced during different steps of the brewing process [109].…”
Section: Perspectives and Concluding Remarksmentioning
confidence: 99%
“…Em geral, a presença de sais na água é desejada e contribui na qualidade da cerveja, conforme exposto na Tabela 1. [46][47][48][49] Ressalta-se que essas informações (Tabela 1) correspondem a parâmetros gerais, os quais podem sofrer alguma variação dependendo do estilo da cerveja. [50][51][52][53][54] O segundo ingrediente utilizado é o cereal.…”
Section: Ingredientes Utilizados Na Produção Da Cervejaunclassified
“…Cho e colaborados 72 produziram cerveja com a adição de caqui, resultando em uma bebida com maior concentração de Mg, K, Ca e flavonoides, apresentando maior atividade antioxidante. Um incremento na atividade antioxidante também foi observado por Ulloa e colaboradores, 48 derivado Coelho Neto, D. M. et al…”
Section: Atividades Biológicas De Compostos Presentes Na Cervejaunclassified
See 1 more Smart Citation